Levitation‒guidance‒propulsion integrated design for maglev trains based on oblique ring Halbach permanent magnet wheels - LIU Xin; DENG Zigang; LIANG Le; LI Kaiwen; LU Hao; ZHENG Jun (机车电传动)
In this paper, a levitation, guidance and propulsion integrated design was proposed for maglev trains on the principle of permanent magnet electrodynamic suspension, in which the Halbach ring permanent magnet wheels and conductor plates were tilted after clockwise rotation. Firstly, the three-dimensional force characteristics of the oblique permanent magnet wheel were analyzed with the ANSYS Maxwell finite element simulation software. According to the simulation results, for a single magnetic wheel with an outer diameter of 200 mm, the oblique angle should not be less than 60 degrees to ensure a buoyancy-weight ratio greater than 5.5 and generate a corresponding propulsive force of 310 N and guiding force of 380 N. Further analysis involved the variation law of the three-dimensional force of the magnetic wheel with the working air gap, conductor plate thickness and conductivity. The three-dimensional force decreased with increasing working air gap. With the increase of the thickness and conductivity of the conductor plate, the suspension force and guiding force increased until reaching saturation, while the propulsion force increased first and then decreased. Based on the above analysis results, a new conceptual model of the levitation, guiding and propulsion integration was presented for maglev trains, and the magnetic wheels with larger diameters and widths were calculated and analyzed. According to the results, the magnetic field utilization rate is the maximum when the diameter is 250 mm in diameter, and the utilization rate is positively correlated with the change in the magnetic wheel width. Applying and extending the permanent magnet electrodynamic suspension theory, the study results can be applied to effectively reduce the construction cost of maglev train systems and provide a reference for the design of new maglev trains with integrated levitation, guidance and propulsion.